Examining the Effect of Brand Trust, Celebrity Endorsement, and Brand Association toward Samsung Mobile Phones Purchase Decisions (Study on Community in Banyumas Regency) - Fauzi, Akhmad; Utami, Restu Frida; Astuti, Herni Justiana; Haryanto, Totok (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2024)
The purpose of this study was to test and analyze the effect of brand trust, celebrity endorsement, and brand association on purchasing decisions for Samsung mobile phones. This study uses quantitative research methods and focuses on people who live in Banyumas. Respondents used in this research sample were 143, which is in accordance with the criteria involved in purchasing decisions for Samsung mobile phones. The data collection method is through a questionnaire distribution survey which is measured on a 5-point Likert scale and analysed through the SPSS 26 application. The results showed that brand trust, celebrity endorsement, and brand association have a positive and significant effect on purchasing decisions for Samsung mobile phones.